Recueillir l’expérience des étudiants dans un dispositif de formation hybride : entre auto-déclaration et learning analytics - Vanessa Marescot; Fanny Bougenies; Sylvie Leleu-Merviel (Distances et Médiations des Savoirs)
The aim of this study is to examine students’ experience of a hybrid training system through their perceptions (N =22), their motivation and their commitment. To this end, a training system can be seen as a space where a life experience takes shape for learners (Leleu-Merviel, 2018). In the context of the life experience, previous research has established that this space becomes a place when the user appropriates it, defining two modes of experience: the visiting experience and the living experience. The collection of user experience, which raises methodological questions, took the form in this study of asynchronous qualitative investigation, making it possible to collect 13 pieces of feedback. The results show that students did not engage with the distance learning part due to a lack of meaning and that face-to-face learning is still of paramount importance: the relational aspect is important for students. The living experience in educational devices appears to be more nuanced than the visiting/inhabiting dichotomy, and will gain in further study, by opening the research to other types of devices.